Minimalist Program and its fundamental improvements in syntactic theory: evidence from Agreement Asymmetry in Standard Arabic - Al-Horais, Nasser (Pragmalingüística, 2012)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The Minimalist Program is a major line of inquiry that has been developing inside Generative Grammar since the early nineties, when it was proposed by Chomsky (1993, 1995). In that time, Chomsky (1998: 5) presents Minimalist Program as a program, not as a theory, but today, Minimalist Program lays out a very specific view of the basis of syntactic grammar that, when compared to other formalisms, is often taken to look very much like a theory. The prime concern of this paper, however, is to provide a comprehensive and accessible introduction to the art of minimalist approach to the theory of grammar. In this regard, this paper discusses some new ideas articulated recently by Chomsky, and have led to several fundamental improvements in syntactic theory such as changing the function of movement and the Extended Projection Principle (EPP) feature, or proposing new theories such as Phases and Feature Inheritance. In order to evidence the significance of these fundamental improvements, the current paper provides a minimalist analysis to account for agreement and word-order asymmetry in Stranded Arabic. This fresh minimalist account meets the challenges (to the basic tenets of syntactic theory) occurred in pre-minimalist analyses.